São Tomé and Príncipe: Particularities of the presidential party - Seibert, Gerhard (2010)
Portuguese constitutionalists were divided about the question of whether the election of President Fradique de Menezes as leader of the Democratic Movement Force of Change (MDFM) party on 19 December was unconstitutional or not.